(untitled) (Research, Society and Development, 2021)
To analyze published scientific evidence on the contributions of nursing care in welcoming adolescents with suicidal ideation. This study is a literature review of the integrative literature review method, carried out in the months between January and June 2021. The search was carried out through the Virtual Health Library Platform - VHL, using the LILACS, BDENF databases , through SCIELO. Adhering through the descriptors/key words: “Nursing Care”, “Suicide”, “Adolescent”, combined with the Boolean operator “AND”. Among adolescents, the main risk factors for suicide are: age, previous attempt, mood disorder, depression, abuse of legal and illegal drugs, lack of family support, family history of psychiatric illnesses, family history of suicidal behavior, illness severe and/or chronic physical, stressful events, sexual orientation. Nursing is responsible for the initial care of patients who attempt suicide, in addition, due to the essence of their activity, which is care, they remain in direct contact with the person being assisted for longer. The nursing team has the potential to help prevent new suicide attempts. It is understood that nursing professionals have a very important role in welcoming patients at risk of suicide and their families. For this, they use tools and strategies such as: mental state examination, risk assessment and classification, patient care in a safe place for both, a support network together with specialized services, family members/caregivers and administration of drug therapy, when necessary, in addition to home visits.